Evaluation of Anti-Toxoplasma gondii Effect of Ursolic Acid as a Novel Toxoplasmosis Inhibitor - Won Hyung Choi; In Ah Lee (MDPI AG, 2018)
This study was carried out to evaluate the anti-parasitic effect of ursolic acid against Toxoplasma gondii (T. gondii) that induces toxoplasmosis, particularly in humans. The anti-parasitic effects of ursolic acid against T. gondii-infected cells and T. gondii were evaluated through different specific assays, including immunofluorescence staining and animal testing. Ursolic acid effectively inhibited the proliferation of T. gondii when compared with sulfadiazine, and consistently induced anti-T. gondii activity/effect. In particular, the formation of parasitophorous vacuole membrane (PVM) in host cells was markedly decreased after treating ursolic acid, which was effectively suppressed. Moreover, the survival rate of T. gondii was strongly inhibited in T. gondii group treated with ursolic acid, and then 50% inhibitory concentration (IC50) against T. gondii was measured as 94.62 μg/mL. The T. gondii-infected mice treated with ursolic acid indicated the same survival rates and activity as the normal group. These results demonstrate that ursolic acid causes anti-T. gondii action and effect by strongly blocking the proliferation of T. gondii through the direct and the selective T. gondii-inhibitory ability as well as increases the survival of T. gondii-infected mice. This study shows that ursolic acid has the potential to be used as a promising anti-T. gondii candidate substance for developing effective anti-parasitic drugs.